2021
DOI: 10.3390/ijerph18199968
|View full text |Cite
|
Sign up to set email alerts
|

Current State of COVID-19 Pandemic in Africa: Lessons for Today and the Future

Abstract: This study is a cross-sectional, observational analysis of the COVID-19 pandemic in Africa, to understand the progression of the disease across the continent. Published data on COVID-19 from 20 January 2020 to 21 June 2021 were obtained and analyzed. Case fatality ratios, as well as case growth rates and other indices were computed. On 21 June 2021, a total of 178,210,532 confirmed cases and 3,865,978 deaths had been recorded worldwide. While the Americas recorded the highest number of cases, Southern Africa r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The globalized view by WHO regions could be extracted from Figure 3 time series plot illustrates the outbreak waves showing major peaks with time. It could be deduced that the west pacific and African followed by East Mediterranean regions were much less in magnitude compared with American, European and Southeast Asian countries [34,44]. This observation confirms the previous finding of the major focus group for the main contributing nations in the Coronavirus morbidities and mortalities [43].…”
Section: Resultssupporting
confidence: 87%
“…The globalized view by WHO regions could be extracted from Figure 3 time series plot illustrates the outbreak waves showing major peaks with time. It could be deduced that the west pacific and African followed by East Mediterranean regions were much less in magnitude compared with American, European and Southeast Asian countries [34,44]. This observation confirms the previous finding of the major focus group for the main contributing nations in the Coronavirus morbidities and mortalities [43].…”
Section: Resultssupporting
confidence: 87%
“…The following extracts support the findings: The extract indicates that emergency health care providers could not give timely treatment due to an unprepared emergency trolley and lack of equipment. The poor supply of resources was also reported in several studies in African countries [2,3]. Furthermore, it was reported that these led to delays in treatment and reporting of COVID-19 patients.…”
Section: Resultsmentioning
confidence: 79%
“…The African continent has recorded the least COVID-19 mortality, with around 170,942 deaths [ 1 ]. Several authors have linked the least amount of death in African countries with under-reporting due to poor health systems and patients’ health-seeking behaviors [ 2 , 3 ], making the use of clinical audit more relevant. South Africa has recorded the highest morbidity and mortality compared to other African regions [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 3.4 billion tests were performed globally from December 2019 to August 2021, most of which were restricted to high-income countries, which conducted more SARS-CoV-2 testing (i.e., USA: 192%, Australia: 146%, Switzerland: 124%, and Canada: 113%) compared to that undertaken in low-income countries (LICs; i.e., Bangladesh: 6%, Uganda: 4% and Nigeria: 1%) ( 20 ). Furthermore, several other factors, such as the fragile healthcare system, relatively low population density, low obesity or diabetes burden, younger population, climate, genetics, and lessons from the public health response to other deadly infectious diseases (e.g., Ebola virus) are correlated with the lower case and death rates observed in Africa ( 21 23 ). Given the selective advantage offered by malaria through a wide distribution of blood group O in Africa, the enormous spread of the angiotensin-converting enzyme II (ACE2) deletion among many African ethnic groups might have reduced COVID-19 susceptibility in Africans ( 24 ).…”
Section: Discussionmentioning
confidence: 99%